2017
DOI: 10.1002/ange.201703591
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Boundaries of Water‐Tolerant Frustrated Lewis Pair Hydrogenation: Enhanced Back Strain in the Lewis Acid Enables the Reductive Amination of Carbonyls

Abstract: The development of ab oron/nitrogen-centered frustrated Lewis pair (FLP) with remarkably high water tolerance is presented. As systematic steric tuning of the boronbased Lewis acid (LA) component revealed, the enhanced back-strain makes water binding increasingly reversible in the presence of relatively strong base.T his advance allows the limits of FLPsh ydrogenation to be expanded, as demonstrated by the FLP reductive amination of carbonyls.T his metal-free catalytic variant displays an otably broad chemosel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…1 N-Benzyl-3,7-dimethyl-6-octenylamine (6). 39 According to general procedure B, starting from (±)-citronellal (0.5 mmol, 1 equiv, 90 μL) and N-benzylamine (0.75 mmol, 1.5 equiv, 90 μL), 6 was isolated, after purification by silica flash column chromatography (7). 40 According to the general procedure A, starting from 3-phenylpropionaldehyde (0.5 mmol, 1 equiv, 70 μL) and morpholine (0.6 mmol, 1.2 equiv, 55 μL), 7 was isolated, after filtration with pentane over a pad of Celite, as a yellowish oil (89 mg, 87%).…”
Section: ■ Experimental Partmentioning
confidence: 99%
“…1 N-Benzyl-3,7-dimethyl-6-octenylamine (6). 39 According to general procedure B, starting from (±)-citronellal (0.5 mmol, 1 equiv, 90 μL) and N-benzylamine (0.75 mmol, 1.5 equiv, 90 μL), 6 was isolated, after purification by silica flash column chromatography (7). 40 According to the general procedure A, starting from 3-phenylpropionaldehyde (0.5 mmol, 1 equiv, 70 μL) and morpholine (0.6 mmol, 1.2 equiv, 55 μL), 7 was isolated, after filtration with pentane over a pad of Celite, as a yellowish oil (89 mg, 87%).…”
Section: ■ Experimental Partmentioning
confidence: 99%
“…9 Alternatively, employing hydrogen as the reductant, Sooś and co-workers developed a boron/nitrogen centered frustrated Lewis pair for the reductive amination of carbonyls (Scheme 1d). 10 Despite the great success that has been achieved, B(C 6 F 5 ) 3 -catalyzed asymmetric reductive amination still remains an unexploited field.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In contrast, in the case of the B(C 6 F 5 ) 3 -catalyzed reaction with aniline, Wei et al proposed an alternative transition state (TS) comprising B(C 6 F 5 ) 3 , PhMe 2 SiH, H 2 O, and N-benzalaniline during the formation of iminium intermediate 4, which was proposed to be involved in the most energetically favorable path based on theoretical calculations (Scheme 8). 14 Interestingly, Ingleson et al also explored the use of H 2 as a reductant in the presence of B(C 6 F 5 ) 3 and confirmed that the targeted N-alkylated amine was not formed, which was subsequently accomplished independently by Sooś et al 15 and Hoshimoto and Ogoshi et al 16 (vide infra).…”
Section: Introductionmentioning
confidence: 96%
“…Sooś et al have recently developed a catalytic reductive Nalkylation of primary and secondary amines with aldehydes and ketones, which was successfully realized in the presence of H 2 by expansion of a water-tolerant FLP strategy (Scheme 10). 15 They demonstrated that three triarylboranes (5−7) catalyzed the reaction between benzaldehyde and benzylamine in the presence of H 2 and molecular sieves in toluene. In addition, 5 is an effective catalyst for the reductive N-alkylation of a variety of alkyl amines, aniline, and p-anisidine, even in the absence of molecular sieves.…”
Section: Introductionmentioning
confidence: 99%